PLGA's Plight and the Role of Stealth Surface Modification Strategies in Its Use for Intravenous Particulate Drug Delivery. Issue 8 (27th January 2022) - Sheffey, Violet V.; Siew, Emily B.; Tanner, Eden E. L.; Eniola‐Adefeso, Omolola
Abstract: Numerous human disorders can benefit from targeted, intravenous (IV) drug delivery. Polymeric nanoparticles have been designed to undergo systemic circulation and deliver their therapeutic cargo to target sites in a controlled manner. Poly(lactic‐ co ‐glycolic) acid (PLGA) is a particularly promising biomaterial for designing intravenous drug carriers due to its biocompatibility, biodegradability, and history of clinical success across other routes of administration. Despite these merits, PLGA remains markedly absent in clinically approved IV drug delivery formulations. A prominent factor in PLGA particles' inability to succeed intravenously may lie in the hydrophobic character of the polyester, leading to the adsorption of serum proteins (i.e., opsonization) and a cascade of events that end in their premature clearance from the bloodstream. PEGylation, or surface‐attached polyethylene glycol chains, is a common strategy for shielding particles from opsonization. Polyethylene glycol (PEG) continues to be regarded as the ultimate "stealth" solution despite the lack of clinical progress of PEGylated PLGA carriers. This review reflects on some of the reasons for the clinical failure of PLGA, particularly the drawbacks of PEGylation, and highlights alternative surface coatings on PLGA particles. Ultimately, a new approach will be needed to harness the potential of PLGA nanoparticles and allow their widespread clinical adoption. Abstract : Biodegradable polymers like PLGA are ideal for constructing intravenously‐administered drug carriers. Nevertheless, intravenous PLGA carriers still lack commercial presence despite numerous publications proposing their use. This review provides a comprehensive overview of stealth coatings that have been tried and assessed with intravenous (IV)‐based PLGA carriers, given that PLGA's hydrophobic nature may play a role in its lack of clinical translation.